1992
DOI: 10.1042/bj2850401
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between glutathione content in liver and glutathione conjugation rate in the rat in vivo. Effect of buthionine sulphoximine pretreatment on conjugation of the two 2-bromoisovalerylurea enantiomers during intravenous infusion

Abstract: The relationship between hepatic glutathione content and hepatic glutathione conjugation rate in the rat in vivo was investigated. As substrate for glutathione conjugation, racemic (R,S)-2-bromoisovalerylurea (BIU) was used which gives rise to the biliary excretion of two diastereoisomeric glutathione conjugates and the urinary excretion of two diastereoisomeric mercapturates. The excretion rate of the glutathione conjugate in bile reflects hepatic conjugation exclusively. An intravenous infusion of BIU was gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Because of the ease by which they are oxidized, mammalian cells sustain millimolar concentrations of these protective non-protein sulhydryls. In rat liver microsomes, and using glutathione concentrations thought to exist in the canine pancreatic ER (i.e., up to and well exceeding 1.0 mM) [47] and liver [25,52,53], GSSG, and GSH to a marginal degree, were found in our study to alter liver microsomal 11␤-HSD1 reductase. Coordinate opposing actions of GSSG and H 2 O 2 on the 11␤-HSD1 dehydrogenase (Fig.…”
Section: Role Of Reactive Oxygen Speciesmentioning
confidence: 62%
“…Because of the ease by which they are oxidized, mammalian cells sustain millimolar concentrations of these protective non-protein sulhydryls. In rat liver microsomes, and using glutathione concentrations thought to exist in the canine pancreatic ER (i.e., up to and well exceeding 1.0 mM) [47] and liver [25,52,53], GSSG, and GSH to a marginal degree, were found in our study to alter liver microsomal 11␤-HSD1 reductase. Coordinate opposing actions of GSSG and H 2 O 2 on the 11␤-HSD1 dehydrogenase (Fig.…”
Section: Role Of Reactive Oxygen Speciesmentioning
confidence: 62%
“…The detoxification of heavy metals by GSH conjugation results in the rapid depletion of GSH in the cytoplasm (Polhuijs et al, 1992). Under these conditions, GSH homeostasis is maintained by the g-glutamyl cycle (Figure 1), which involves GSH synthesis and degradation, and the recycling of the component amino acids Glu, Cys, and Gly (Griffith et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies, however, have shown that a high degree of GSH depletion is required to have any effect on the rate of substrate conjugation (Mulder and Ouwerkerk‐Mahadevan 1997). Indeed, according to Polhuijs et al . (1992) hepatic levels of GSH must be reduced to below 1 µmol/g tissue before significantly affecting the conjugation rate.…”
Section: Discussionmentioning
confidence: 99%